PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR SEJARAH SISWA KELAS XI SMA MUHAMMADIYAH 2 PALEMBANG - Yusinta Tia Rusdiana; Nur Ramadhan; Yayan, Yayan (SEHRAN (Jurnal Pendidikan Sejarah dan Kewarganegaraan), 2024)
This research is motivated by the low learning outcomes of students which are still below the KKM. The reason is that teachers still use conventional methods so that students only chat and do not focus on following the learning in class. So that a learning model is needed that can help teachers to explain a material or facilitate students to be more creative in learning, namely the discovery learning model which is applied in the history learning process. The formulation of this research is (1) How is the process of implementing the discovery learning model (2) Constraints faced in implementing the discovery learning model (3) The effect of the discovery learning model on the learning outcomes of class XI history students at SMA Muhammadiyah 2. The method used in the study is a quasi-experimental method. Data collection techniques use observation, interviews, documentation and tests. Data analysis uses normality, validity, reliability and hypothesis tests. The conclusion of the study obtained (1) the final thesis results, it is known that the results of learning history of class XI S1 (XII S1) experienced changes, namely 27 students who got a score of ≥ 70 (complete), (2) The obstacles faced were conveying the idea of ​​formulating problems and designing hypotheses in the material of the forced cultivation system to students, because it was already patterned with conventional monotonous learning. (3) There is a significant influence of the discovery learning model on the results of learning history of class XI students of SMA Muhammadiyah 2 Palembang, this is proven by the value of 80.9.